Suitability of Cu-BTC extrudates for propane-propylene separation by adsorption processes - Alexandre F. P. Ferreira (2011)
In this work, we investigate the potential of a MOF porous material, Cu-BTC in combination with cyclic adsorption processes (vacuum swing adsorption, VSA, and simulated moving bed, SMB) for the separation of propylene/propane mixture. A gravimetric method has been used to measure the adsorption isotherms of propylene, propane and isobutane onto Cu-BTC extrudates over a temperature range from 323 to 373 K and pressures up to 500 kPa. These were complemented by experimental characterization of the Cu-BTC material using XRD and SEM-EDS techniques. Whereas the separation and its kinetics were studied by breakthrough experiments on a column packed with the Cu-BTC material in the extruded form at 373 K. The Cu-BTC extrudates are selective towards propylene, highlighting the potential of this material for the separation of propane and propylene mixtures by PSA process. Furthermore, in a range of temperatures and pressures, the affinity of Cu-BTC for isobutane was observed to be intermediate to that of propane and propylene which suggest that isobutane is a promising desorbent in SMB processes for propane/propylene separations.